2018
DOI: 10.1002/clen.201700071
|View full text |Cite
|
Sign up to set email alerts
|

Saponin Versus Rhamnolipids for Remediation of Cd Contaminated Soils

Abstract: Cadmium should be effectively removed from soil because it is one of the most toxic soil pollutants. Thus, the present study compared a plant (saponin, SAP) and a microbial (rhamnolipids, RAM) biosurfactant for Cd removal from three different types of soil. Batch washing was tested under different operational conditions: Biosurfactant concentration, 0.1–10% SAP, 0.01–1% RAM; washing time, 0.1–6 h; soil dosage, 12.5–100 g L−1; biosurfactant pH, 2–9 for SAP, 5.5–12 for RAM; washing number, three with SAP, four w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…2). This is in agreement with previous studies (Wei et al 2016;Kulikowska et al 2015;Gusiatin and Radziemska 2018). With regard to most HMs (i.e., Zn, Ni, Cu), sequential soil washing with plant biosurfactants (SAP-SAP or TAN-TAN) removed more HMs than sequential soil washing with microbial biosurfactants (RAM-RAM).…”
Section: The Effect Of Sequential Soil Washing With Biosurfactants Onsupporting
confidence: 92%
“…2). This is in agreement with previous studies (Wei et al 2016;Kulikowska et al 2015;Gusiatin and Radziemska 2018). With regard to most HMs (i.e., Zn, Ni, Cu), sequential soil washing with plant biosurfactants (SAP-SAP or TAN-TAN) removed more HMs than sequential soil washing with microbial biosurfactants (RAM-RAM).…”
Section: The Effect Of Sequential Soil Washing With Biosurfactants Onsupporting
confidence: 92%
“…Five operating factors surfactant concentration, washing time, agitation speed, soil solution pH and airflow rate are selected and optimized. Soil properties like soil texture, organic matter content, mineral composition of the soil and pH significantly affect its contaminant desorption rate (Gusiatin & Radziemska, 2018). We also validate and compared the optimized operating factors under different soil textural classes, organic matter levels and age of contamination between aerated and non-aerated soil washing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…PTEs content in the solution of the extractants (Table 3) showed that CDs have no statistically significant effect compared to water extraction capacity, whereas RL actually increased PTEs content on extracting solution significantly (Cr, Cu, Fe, Mn, Ni, Pb and Zn). No Journal Pre-proof J o u r n a l P r e -p r o o f extraction was detected for Cd, although RL has been described as a good extractant for Cd in contaminated soils (Gusiatin and Radziemska, 2018). The highest PTEs extractable contents were found for Fe > Mn > Ni > Zn, and the increases were especially notorious for Fe and Ni (around 10 and 50-fold higher respectively compared to water extraction).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 94%